EFEK PENAMBAHAN ANTIOKSIDAN TERHADAP SIFAT SENSORI DAN LAMA SIMPAN ROTI TAWAR YANG DIFORTIFIKASI DENGAN MINYAK IKAN [The Effect of Addition of Antioxidant to Sensory Characteristic and Shelf Life of Bread Fortified by Fish Oil] - Sugiharto, Ribut; Koesoemawardhani, Dyah; Apriyani, Tias (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2016)
White bread is the kind of food which contains high carbohydrates content, but it does not have omega-3 fatty acids. The composition of omega-3 fatty acids can be increased by fortification with fish oil, as a source of omega-3 fatty acids. However, the fish oil is very susceptible to oxidation, which causes changes in aroma and flavor, as well as affect the shelf life of the bread. Therefore, addition of antioxidants into white bread fortified with fish oil is needed to maintain the sensory properties and extend the shelf life of the bread. This study aimed to get the right combination of adding antioxidants to maintain the sensory properties and extend the shelf life of the white bread fortified with fish oil. The research was arranged in Randomized Block Design Complete (RBDC) with two factors, that were combination of ascorbic acid and BHA (0% and 0,02% w/w; 0,005% w/w and 0,015% w/w; 0,01% w/w and 0,001% w/w; 0,0015% w/w and 0,005 w/w; and 0,02% w/w and 0, respectivelly), and storage time (0, 3, and 6 days). All the data from the experiment were analyzed by Bartlett Test for equality of variance and Tukey Test for data additivity. The data were analyzed by Analyzed of Variant to get the error variance estimators and differences between treatments. The data were analyzed further by LSD Test to determine the best treatment. The result showed that addition of the 0,010% w/w of ascorbic acid and 0,010% w/w of BHA into fortified bread produced the bread that had the best organoleptic properties and the lowest peroxide value. Additionally, such treatment produced the bread that could be stored for 3 days without changing its organoleptic properties significantly.Key words: fish oil, fortification, omega-3, white bread.